Tindak Tutur Ilokusi dalam Tayangan Catatan Demokrasi di Tv One - Sherli Sherli; Hermaliza Hermaliza (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Illocutionary speech act other than giving information about something. The problem in this study is how are Illocutionary Speech Acts in Democracy Notes on Tv One? The purpose of this study is to describe the illocutionary speech acts contained in the Democracy Notes Program on Tv One. The approach in this research is a qualitative approach with content analysis method. Based on the research results, it can be concluded that there were 150 data containing illocutionary speech acts. Then from the five forms of illocutionary speech acts the writer only found four illocutionary speech acts, namely, assertive, directive, commissive, and expressive. Assertive speech acts were found in 106 speech data. Directive illocutionary speech acts found 30 speech data. There are 3 commissive illocutionary speech acts in data, and 11 utterances found in expressive illocutionary speech acts. While declarative illocutionary speech acts were not found.